PROFILE IMMUNOGLOBULIN M (IgM) BALI CATTLE IN NUSA PENIDA KLUNGKUNG DISTRICT BALI PROVINCE - Laksmi, Luh Kadek Nanda; Besung, I Nengah Kerta; Suartha, I Nyoman; Suwiti, Ni Ketut (Buletin Veteriner Udayana; Vol. 11 No. 1 Pebruari 2019DO - 10.24843/bulvet.2019.v11.i01.p14, 2019)
This study aims to determine the profile of immunoglobulin M (IgM) of bali cattle in Nusa Penida. The serum samples of 54 bali cattle that were kept in Nusa Penida based on geographical criteria consisted of highlands (Klumpu and Batumadeg villages) and lowlands (Ped villages), age covering young bali cattle (12-18 months ) and adults (24 months and over), while sex (male and female). The serum obtained was tested using the ELISA (Enzyme Linked Immunosorbent Assay) method. The results showed that 54 samples of serum of bali cattle in Nusa Penida were detected in the presence of levels of immunoglobulin M (IgM) with values ranging from 2.565 ng/mL – 8.834 ng/mL. The mean rate of serum IgM cattle raised in the lowlands (4,837 ± 1,385 ng / mL) was descriptively higher than in the highlands (4,761 ± 1,353 ng / mL), while for female bali cattle (5.018 ± 1.370 ng / mL) higher than male (4,477 ± 1.290 ng / mL), while adult bali cattle (4,869 ± 1.417 ng / mL) was higher than young bali cattle (4,707 ± 1.305 ng / mL), but statistically comparable from all categories showed no significantly (P> 0.05). The average rate of IgM of bali cattle maintained in Nusa Penida can be used as a data base of IgM profile of bali cattle that is maintained in Nusa Penida.